Serum Magnesium Levels in Patients Admitted with Septic Shock and Its Correlation with Outcome - Premita, Mayengbam; Ajaykumar, Rajkumar; Kireeti, P.; Singh, Seram (International Journal of Integrated Health Sciences, 2024)
Objective: To evaluate the initial serum magnesium levels of critically ill septic shock patients upon admission to the intensive care unit (ICU) and correlate these levels with the patients' requirements and outcomes, including ventilator support, length of stay in the ICU, occurrence of cardiac arrhythmias, and mortality rates.Methods: This was an observational study involving 60 patients who were admitted to the medical Intensive Care Unit (ICU) for septic shock. Serum magnesium levels were measured upon admission to the ICU. A comparison was made between patients with normal and abnormal magnesium levels at the time of admission to evaluate the need for vasopressor support, the average duration of assisted ventilation and dialysis, the incidence of arrhythmia, the average length of ICU stay, and mortality rates.Results: Out of the 60 cases studied, there were 42 males (70.00%) and 18 females (30.00%), resulting in a M:F ratio of 1:0.42. The mean age of both male and female patients was found to be comparable. The need for assisted ventilation and renal replacement therapy was found to be comparable in patients with normal and abnormal serum magnesium levels. The number of days for which assisted ventilation was required, the incidence of arrhythmia, the mean duration of ICU and hospital stay, and mortality were significantly higher in patients with abnormal magnesium levels at the time of ICU admission (P<0.05).Conclusion: Abnormal serum magnesium levels are associated with increased morbidity and mortality in critically ill septic shock patients admitted to the ICU.